Screen distractions and vocabulary gains in Memrise mobile-assisted vocabulary learning (MAVL) setting - Azwar Abidin (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2023)
Despite the significance of investigating the impact of screen distractions on mobile-assisted vocabulary learning (MAVL), research in this area is limited. This experimental study investigated the impact of screen distractions on participants Memrise MAVL experience. It employed an exploratory case study design in an EFL flipped classroom setting and examined the impact of a two-week Memrise MAVL experience on participants' vocabulary gains, time spent on the process, engagement with screen activities, and the effect of screen distractions. The results showed no significant differences in the completion of target units between the control and experimental groups. However, there was a significant difference in the total amount of screen distractions among individuals in both groups. The study also found significant correlations between participants total finished target words and other dependent variables. The linear regression test indicated a strong correlation between total screen distractions and participants' finished target words. Although screen distractions did not significantly affect individual performance on vocabulary gains, they did contribute to the total time spent on the process. Overall, this study highlights the potential of mobile-based apps in self-directed and independent vocabulary learning within the flipped classroom setting.